RESEARCH OF MODERN BORROWED VOCABULARY IN ENGLISH, GERMAN AND UZBEK (Spectrum Journal of Innovation, Reforms and Development, 2024)
The article is an overview of studies of modern borrowed vocabulary in English, German and Uzbek languages. The article discusses different approaches to the study of borrowed vocabulary in the 21st century. The main purpose of the review is to identify the least studied area in the research of foreign language vocabulary in English, German and Uzbek languages. In connection with globalization and the expansion of trade and economic relations between countries, economic terminology is of particular interest to us. Many economic terms are the result of borrowing, as changes in the global economy are reflected in the lexical composition of the language.